Assessing interference in isobaric tag‐based sample multiplexing using an 18‐plex interference standard. Issue 7 (14th January 2022) - Navarrete‐Perea, Jose; Liu, Xinyue; Rad, Ramin; Gygi, Jeremy P.; Gygi, Steven P.; Paulo, Joao A.
Abstract: Reporter ion interference remains a limitation of isobaric tag‐based sample multiplexing. Advances in instrumentation and data acquisition modes, such as the recently developed real‐time database search (RTS), can reduce interference. However, interference persists as does the need to benchmark upstream sample preparation and data acquisition strategies. Here, we present an updated Triple yeast KnockOut (TKO) standard as well as corresponding upgrades to the TKO viewing tool (TVT2.5, http://tko.hms.harvard.edu/ ). Specifically, we expand the TKO standard to incorporate the TMTpro18‐plex reagents (TKO18). We also construct a variant thereof which has been digested only with LysC (TKO18L). We compare proteome coverage and interference levels of TKO18 and TKO18L data that are acquired under different data acquisition modes and analyzed using TVT2.5. Our data illustrate that RTS reduces interference while improving proteome coverage and suggest that digesting with LysC alone only modestly reduces interference, albeit at the expense of proteome depth. Collectively, the two new TKO standards coupled with the updated TVT represent a convenient and versatile platform for assessing and developing methods to reduce interference in isobaric tag‐based experiments.